IDENTIFIKASI POTENSI WISATA DI DESA PIPIT TEJA DALAM MENDUKUNG TERWUJUDNYA DESA WISATA PIPIT TEJA DI KABUPATEN SAMBAS - Nurchalis, Nurchalis (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
Pipit Teja is a village located in Teluk Keramat sub-district, Sambas Regency that ha s tourism potential from culture, nature and man-made that can be developed into a tourism destination. This village has human resources that have the potential to develop the area. This research is an action research conducted by mapping the tourism potential in Tebing Jaya Village through a study of the potential of natural, artificial, and cultural tourism attractions and measuring the level of readiness to become a tourist attraction. The potential of tourist attraction is an important capital to make Pipit Teja village towards a Tourism village in Sambas Regency in order to improve the economic level of the village community. Data collection methods by means of observation, interviews, and documentation with purposive sampling techniques on the Village Government, community leaders, and Traditional Leaders. The data analysis technique uses qualitative technique analysis. The results found that Pipit Teja village has natural, cultural and artificial tourism potential. Natural potential is rice fields, while cultural potential is Berattep, Beraddad, and Dhikr. Furthermore, artificial potential consists of cafes, children's playgrounds, bird song competitions, sports competitions such as playing dynasty and futsal competitions. These three potentials can be developed because they will be the reason for outsiders to visit Pipit Teja village. Pipit Teja village has tourism potential that is very potential to be developed towards Pipit Teja village as a Tourism Village.